THE INFLUENCE OF FAMILY ENVIRONMENT ON THE MANIFESTATION OF GUILT FEELINGS IN STUDENTS ABSTRACT (Eureka Journal of Education & Learning Technologies, 2026)
This article discusses the manifestation of guilt feelings in students and the influence of the family environment on their development. Guilt is considered a relatively less painful emotional experience compared to shame, which is associated with the negative evaluation of one’s personal traits. Guilt is typically accompanied by feelings of repentance, apology, and remorse.
Keywords: Guilt, manipulation, emotionality, feelings, existential-ontological, reflexivity.